2020
DOI: 10.1177/0885328219899233
|View full text |Cite
|
Sign up to set email alerts
|

Layered hydroxide/polydopamine/hyaluronic acid functionalized magnesium alloys for enhanced anticorrosion, biocompatibility and antithrombogenicity in vascular stents

Abstract: Magnesium alloys are promising cardiovascular stent materials due to the favourable physical properties and complete biodegradability in vivo. However, the rapid degradation, poor cytocompatibility and tendency of thrombogenesis hinder practical clinical applications. In order to solve these problems, a facile and highly efficient strategy of alkali treatment combined with subsequent layer-by-layer assembly was used to fabricate a multifunctional coating. A bottom layer hydroxyl (–OH) with negative charge afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
(66 reference statements)
0
13
0
Order By: Relevance
“… AZ31 MAO/PLLA/PDA/Hep SBF −1.623 −1.483 69.51 0.5581 1.588 0.0127 The composite coating improved the surface hemocompatibility enhanced the HUVECs proliferation and simultaneously inhibited the SMCs proliferation [ 94 ]. AZ31B Mg(OH) 2 /PDA/HA SBF −1.682 −1.399 14.40 7.37 0.329 0.168 8 Mg(OH) 2 /PDA/HA coating showed a distinct amelioration in corrosion resistance, anti-thrombotic properties, and biocompatibility [ 237 ]. JDBM LDH/Mg(OH) 2 2.6 PBS −1.7749 −1.5277 15.62 0.3626 0.356 0.0083 30 LDH/Mg(OH) 2 exhibited favorable corrosion resistance and cell adhesion, migration, and proliferation in vitro.…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“… AZ31 MAO/PLLA/PDA/Hep SBF −1.623 −1.483 69.51 0.5581 1.588 0.0127 The composite coating improved the surface hemocompatibility enhanced the HUVECs proliferation and simultaneously inhibited the SMCs proliferation [ 94 ]. AZ31B Mg(OH) 2 /PDA/HA SBF −1.682 −1.399 14.40 7.37 0.329 0.168 8 Mg(OH) 2 /PDA/HA coating showed a distinct amelioration in corrosion resistance, anti-thrombotic properties, and biocompatibility [ 237 ]. JDBM LDH/Mg(OH) 2 2.6 PBS −1.7749 −1.5277 15.62 0.3626 0.356 0.0083 30 LDH/Mg(OH) 2 exhibited favorable corrosion resistance and cell adhesion, migration, and proliferation in vitro.…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…One such development is available for magnesium-based stents, which can be improved through alkali treatment followed by polydopamine and hyaluronic acid immobilization via strong electrostatic adsorption and covalent bonding between the carboxyl group of hyaluronic acid and the amine or hydroxyl groups of polydopamine. Hence, a magnesium/OH/polydopamine/hyaluronic acid coating can be obtained, the optimum biocompatibility–antithrombogenicity balance of which is achieved by adjusting the hyaluronic acid content on the polydopamine surface [ 178 ].…”
Section: Stent Optimizationmentioning
confidence: 99%
“…Another attractive approach is to covalently bond the elastomeric polymer on Mg alloys to control the corrosion as well as increase the strength of adhesion of the coating on the substrate, but this can be difficult as the frequently used polymers, such as PLGA, PCL, PLLA lack adequate reactive functional groups to bond on Mg alloys. In some recent studies, polymer coatings were covalently attached on Mg alloys aimed at cardiovascular stent application [26,28,29], and some of these results confirmed that the coatings were adhered well on the substrate, reduced the degradation rate of Mg alloys, and exhibited good hemocompatibility.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous coatings with corrosion control, anti-hyperplasia, and/or anti-thrombogenic properties have been implemented on Mg surface, which include titanium dioxide (TiO 2 ) [12], heparin functionalized coatings [13][14][15][16], nanoscale MgF 2 coating [17], MgF 2 /polydopamine coating [18], catechol conversion coating [19,20], silk fibroin coating loaded with drug [21], polymer coatings with anti-proliferative drugs [22][23][24] and without drug loading [25,26], plasma treatment [27], and others [28,29]. However, few of these options have been reported to have surface erosion properties.…”
Section: Introductionmentioning
confidence: 99%